Utility of signs and symptoms of chronic cough in predicting specific cause in children - Marchant, J M (BMJ Group, 2006)
BACKGROUND: Paediatricians rely on cough descriptors to direct them to the level of investigations needed for a child presenting with chronic cough, yet there is a lack of published data to support this approach. A study was undertaken to evaluate (1) whether historical cough pointers can predict which children have a specific cause for their cough and (2) the usefulness of chest radiography and spirometry as standard investigations in children with chronic cough. METHODS: This was a prospective cohort study of children referred to a tertiary hospital with a cough lasting >3 weeks between June 2002 and July 2004. All included children completed a detailed history and examination using a standardised data collection sheet and followed a pathway of investigation until a diagnosis was made. RESULTS: In 100 consecutively recruited children of median age 2.8 years, the best predictor of specific cough observed was a moist cough at the time of consultation with an odds ratio (OR) of 9.34 (95% CI 3.49 to 25.03). Chest examination or chest radiographic abnormalities were also predictive with OR 3.60 (95% CI 1.31 to 9.90) and 3.16 (95% CI 1.32 to 7.62), respectively. The most significant historical pointer for predicting a specific cause of the cough was a parental history of moist cough (sensitivity 96%, specificity 26%, positive predictive value 74%). CONCLUSIONS: The most useful clinical marker in predicting specific cough is the presence of a daily moist cough. Both chest examination and chest radiographic abnormalities are also useful in predicting whether children have a specific cause of their cough.